Kajian Simpanan Biji Pala Oleh Petani Di Desa Morela Kecamatan Leihitu Maluku Tengah - Ummi Duwila; Andre Sapthu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The habit of storing the harvest in the form of nutmeg is something that has become a culture among the people of Morela village, Leihitu District, Central Maluku Regency. This research will examine theoretically the economic variables that influence the storage of dry nutmeg seeds by farming households. To analyze the relationship between variables that cause savings choices, an inter-time model is used. The choice is based on the meaning of the present and future times. If the present time is more meaningful then farmers will sell the nutmeg seeds they have and conversely if the future time is more meaningful it will increase the amount of nutmeg savings. The variables included in this research are relative price variables, current income and future income. This research uses primary data through interviews and questionnaires. The samples taken based on the purposive random sampling method were 75 farmers in Morela village. To analyze the magnitude of the influence of the independent variable on the dependent variable, cross-section regression was used using the Eviews tool. The results of the research show that the price variables at harvest, the estimated future price of cloves, and future consumption influence the clove savings of farmer households.